Produto assistivo para crianças com deficiência visual: estudo de caso do projeto de um jogo de tabuleiro - Vieira, Higor Freitas Arrebola (Universidade Federal de São Carlos, 2021)
Games are playful means of developing skills and can contribute to the cognitive, motor and social field of children, including those with some type and degree of visual impairment. The aim of this article is to validate the concept of a board game for visually impaired children and, for that, a case study of an assistive product prototype elaborated in the discipline of Design and Development of Sustainable Products and Processes was carried out. Production Engineering course at a Public University of the State of São Paulo. They were explained in order to understand the participants' perception about the developed project and validate its concept. The results indicated the approval of the concept mainly for the following reasons: to promote the integration of visually impaired children and visionaries; for the simplicity of the game, highlighting a differential for the issue of low cost; for being easy to learn and playful. Some improvements were even suggested to increase the ease of use. It was concluded that inclusive games can influence a fairer society and encourage the development of children with or without visual impairment.
Assistive resource for visually impaired children: case study of a board game design
Keywords: Tecnologia assistiva; Inclusão; Jogo; Deficiência visual; Assistive product; Skills; Board game; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS